UJI EFEKTIFITAS ANTIMIKROBA MENGGUNAKAN HAND SANITIZER BERBAHAN DASAR ALAMI PIPER BETLE L. DAN ALOE VERA - Muthi'ah Irbah (Jurnal Kesehatan Masyarakat Indonesia, 2022)
Hands are one of a part of the body that are susceptible to pathogenic microorganisms and non-pathogenic microorganisms. Therefore, keeping hands clean is very important to prevent illness, one of which is using hand sanitizer. Chemical-based hand sanitizers often cause skin problems, so there is an innovation about creating a natural-based hand sanitizer. Piper betle L. and aloe vera were chosen as the basic ingredients for making natural-based hand sanitizer because they have antimicrobial properties and are easy to find in the community; This study aims to determine the effectiveness of antimicrobial using natural-based hand sanitizer of Piper betle l. and Aloe vera; The study was conducted in September 2021 with 25 students of Medical studies program from 2018 and 2019 classes as the sample. The method used in this study was an experimental quantitative analysis with a design using Pre-Test Post-Test One Group Design; The results showed a decrease in microorganisms on hands in 23 students. The average number of colonies of microorganisms using natural-based hand sanitizers of betel leaf and aloe vera is 1114.64 (before) and 504.64 (after). It can be concluded that the natural-based hand sanitizer of betel leaf and aloe vera is effective as an antimicrobial.Keywords: hand sanitizer, betel leaf, aloe vera